A Comprehensive study on Internet of Things Applications and Challenges - Thakur, A (International Journal of Computer Sciences and Engineering, 2022)
The Internet of Things (IoT) is basically viewed as a system which consists of smart objects with various sensors, networks, & processing technologies. IoT transforms the way internet works and carries together the domains such as big data technologies, communication between different machines, artificial intelligence etc. to work underneath the similar canopy so that internet and humans are entangled together. Hence IoT offers pervasive computing giving growth to cyber systems. IoT is an integrated system and works collectively to offer smart services to the end-users. IoT gives several advantages to us by an environment where smart services are offered to use any activity anytime & anywhere. These smart services are offered through different applications executing in the IoT environment. IoT applications monitor & consequently assist in fast decision-making process for client management. In the present work, the different approaches of IoT and its applications unfolding the key components and features are presented. The present work also explores IoT challenges.